2006
DOI: 10.1093/ndt/gfi323
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of habitual physical activity in chronic haemodialysis patients

Abstract: Low habitual physical activity assessed in HD patients with simple portable pedometers is strongly related to several factors of major clinical importance in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
55
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 20 publications
9
55
1
1
Order By: Relevance
“…Belik et al 8 and Medina et al 21 rated the PAL of HD patients using the IPAQ and observed a prevalence of 74.5% and 72.3%, respectively, of sedentary and insufficiently active individuals. Although the studies have used other instruments 5,9,15 for the assessment of the PAL, the results obtained corroborate the low PAL found in this study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Belik et al 8 and Medina et al 21 rated the PAL of HD patients using the IPAQ and observed a prevalence of 74.5% and 72.3%, respectively, of sedentary and insufficiently active individuals. Although the studies have used other instruments 5,9,15 for the assessment of the PAL, the results obtained corroborate the low PAL found in this study.…”
Section: Discussionsupporting
confidence: 89%
“…The results of this study demonstrated a high prevalence of sedentary patients, which, according Zamojska et al 15 , is a common feature of HD patients, possibly due to the loss of strength, muscle atrophy and impaired muscle fibers. Belik et al 8 and Medina et al 21 rated the PAL of HD patients using the IPAQ and observed a prevalence of 74.5% and 72.3%, respectively, of sedentary and insufficiently active individuals.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This simple method, which is validated and widely used in sports and preventive medicine (13,15), accurately assesses habitual physical activity. Recent studies that measured the habitual physical activity of HD patients with accelerometers or pedometers (14,(16)(17)(18) have shown that physical activity is significantly lower in HD patients than in age-matched healthy controls (16,17) and that physical activity in HD patients declines gradually (19). Kutsuna et al reported that maintaining a high level of physical activity in daily living for HD patients is important for preventing the deterioration of walking ability (20).…”
Section: Introductionmentioning
confidence: 99%
“…De fato, ao avaliar o nível de atividade física, definido pela razão entre GET/GER, mostrou-se que essa razão nos pacientes em HD (entre 1,3 e 1,4) era compatível com um estilo de vida sedentário 26,27 , segundo os pontos de corte propostos pela World Health Organization (WHO) 11 . Corroborando esses achados, trabalhos anteriores já apontavam essa reduzida atividade física nos pacientes em HD em relação a indivíduos saudáveis, quando estudados por métodos indiretos, como pedômetro e acelerômetro 29,30 . Dessa forma, não há dúvida de que o sedentarismo é um achado comum em pacientes em hemodiálise.…”
Section: Efeito Térmico Dos Alimentos E Gasto Energético Para Atividaunclassified